Factors associated with the presence of microangiopathy in type 2 diabetics outpatients in Antananarivo, Madagascar, in 2023 - Raherison, Rija E.; Razanamparany, Thierry; Andrianiaina, Miora M. A.; Andrianasolo, Radonirina L.; Rakotomalala, Andrianirina D. P. (International Journal of Research in Medical Sciences, 2025)
Background: The microvascular complications of diabetes correspond to diabetic microangiopathy including retinopathy, nephropathy and neuropathy. Few data are available on diabetic microangiopathy in Madagascar. The aims of the present study were to determine the prevalence of microangiopathy and their associated factors in a population of type 2 diabetics seen as outpatients in the Endocrinology Department of Joseph Raseta Befelatanana Hospital, in Antananarivo, Madagascar. Methods: Cross-sectional, descriptive and analytical study was conducted over a 6-month period. Retinopathy was diagnosed by specific abnormalities on fundus examination, nephropathy by albuminuria ≥30 mg/24h, and peripheral neuropathy by symmetrical distal sensory symptoms beginning in the lower limbs, a DN4 score ≥4/10 and/or impaired foot sensitivity. Results: Of the one hundred type 2 diabetics included in the study, sixty-two (62%) had presented with one or more diabetic microangiopathy. Associated factors were diabetes duration ≥10 years (OR=3.28; 95% CI: 1.17-9.22), abdominal obesity (OR=1.72; 95% CI: 1.06-2.77) and HbA1c >10% (OR=3.72; 95% CI: 1.02-13.48). Albuminuria was significantly higher in type 2 diabetics with microangiopathy than in without (p<0.01) while estimated glomerular function rate was significantly lower (p=0.04). Conclusions: Diabetic microangiopathy was frequent. Optimal management of hyperglycemia, obesity and associated cardiovascular risk factors is essential to avoid or limit their occurrence.